Evaluation and Segmentation of Printing Accessories Suppliers Based on the Integration of the Best Worst Method and Fuzzy TOPSIS (Case Study at PT. Udaka Indonesia) - Wakhid Nur Hidayat; Elly Wuryaningtyas Yunitasari; Patrisius Edi Prasetyo (OPSI, 2021)
In an increasingly competitive industrial environment, every company strives to increase the quality and efficiency of its product development process. PT. Udaka Indonesia, a clothing manufacturer, is experiencing raw material shortages that disrupt the company's production process. The goal of this research is to assess and segment the company's suppliers. The Best Worst Method (BWM) is employed for weighting criteria, and Fuzzy TOPSIS is used to rank alternative providers and subsequently segment them. The dimensions of capabilities (8 criteria with 26 sub-criteria) and willingness (4 criteria with 15 sub-criteria) make up the company's supplier evaluation criteria. The evaluation results suggest that suppliers A2, B2, C2, and D2 are the best in terms of capabilities for label accessories, stickers, paper tags, and polybags, respectively, while A1, B2, C2, and D2 are the best in terms of willingness. Supplier segmentation results show that segmentation 1 includes suppliers C1, B1, B3, and D1, segmentation 2 includes supplier A3, and segmentation 4 includes suppliers A1, A2, B2, B4, C2, and D2.